2015
DOI: 10.12938/bmfh.2014-012
|View full text |Cite
|
Sign up to set email alerts
|

Poultry-beneficial solid-state Bacillus amyloliquefaciens B-1895 fermented soybean formulation

Abstract: Birds were given a new formulation of the Bacillus amyloliquefaciens B-1895 solid-state fermented soybean that retained the spores of the aforementioned organism. Mass dynamics, feed flow rate and broiler performance were observed to evaluate the efficacy of the formulation. At each time point, the live mass was greater than that of the control group, reaching a difference of 7–8% by day 28. A difference of 5.3–8.8% was observed in feed conversion per kilogram live mass (1.97 kg in the controls as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Positive health effects were noticed such as increment food consumption and increasing of broilers' body weight [13]. An association between Bacillus-food supplements and immune system stimulation was identified in chicken.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Positive health effects were noticed such as increment food consumption and increasing of broilers' body weight [13]. An association between Bacillus-food supplements and immune system stimulation was identified in chicken.…”
Section: Discussionmentioning
confidence: 95%
“…B. amyloliquefaciens B-1895 strain was reported as a putative probiotic in poultry and fish [13]. Based on the beneficial properties of both microorganisms, we hypothesize on their possible use as probiotics for human and/or agricultural applications.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…and AlGburi et al . demonstrated that B. amyloliquefaciens B2 and B. amyloliquefaciens B‐1895 were able to tolerate exposure for 2 h and 4 h, respectively, to bile at a concentration of 3 g L −1 . Overall, our results showed that the B. amyloliquefaciens US573 strain exhibits good tolerance to acid pH and bovine bile.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, probiotic preparation Ecobiol ® based on Bacillus amyloliquefaciens CECT5940 spores reduces the effect of the pathogenic bacteria Clostridium perfringens and Escherichia coli, and to improve the feed conversion rate in poultry (EFSA 2008). Recently, we have shown that Bacillus amyloliquefaciens B-1895 spores obtained after soybean solid-state fermentation stimulate the broilers' growth, improve feed conversion rate and body weight gain and quality (Chistyakov et al, 2015). Moreover, performed safety tests for toxigenic and mutagenic potential, co-aggregation capability with Escherichia coli and Pseudomonas aeruginosa, antibiotic resistance, tolerance to incubation at 0.3% bile salts and at pH 2.0-3.0 revealed a high potential of this strain for food and medical applications (AlGburi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%